A literature review on energy efficiency standards and labels for household electrical appliances - Masjuki, Haji Hassan; Mahlia, T.M.I.; Choudhury, I.A.; Saidur, Rahman (IEEE, 2000)
This is a summarized previous works on energy efficiency standards and labels for household electrical appliances. It concerns mostly about international situation and other country experience about energy efficiency standard in residential sector. The possibilities of implementation of standards and labels for various household electrical appliances in Malaysia are also discussed. From the international review and other country experience shown that; there are many advantages for Malaysia to implement the standards and labels for household electrical appliances.